Platelet-Derived Growth Factor Receptor Association with Na(+)/H(+) Exchanger Regulatory Factor Potentiates Receptor Activity - Maudsley, Stuart (American Society for Microbiology, 2000)
Platelet-derived growth factor (PDGF) is a potent mitogen for many cell types. The PDGF receptor (PDGFR) is a receptor tyrosine kinase that mediates the mitogenic effects of PDGF by binding to and/or phosphorylating a variety of intracellular signaling proteins upon PDGF-induced receptor dimerization. We show here that the Na(+)/H(+) exchanger regulatory factor (NHERF; also known as EBP50), a protein not previously known to interact with the PDGFR, binds to the PDGFR carboxyl terminus (PDGFR-CT) with high affinity via a PDZ (PSD-95/Dlg/Z0-1 homology) domain-mediated interaction and potentiates PDGFR autophosphorylation and extracellular signal-regulated kinase (ERK) activation in cells. A point-mutated version of the PDGFR, with the terminal leucine changed to alanine (L1106A), cannot bind NHERF in vitro and is markedly impaired relative to the wild-type receptor with regard to PDGF-induced autophosphorylation and activation of ERK in cells. NHERF potentiation of PDGFR signaling depends on the capacity of NHERF to oligomerize. NHERF oligomerizes in vitro when bound with PDGFR-CT, and a truncated version of the first NHERF PDZ domain that can bind PDGFR-CT but which does not oligomerize reduces PDGFR tyrosine kinase activity when transiently overexpressed in cells. PDGFR activity in cells can also be regulated in a NHERF-dependent fashion by stimulation of the β(2)-adrenergic receptor, a known cellular binding partner for NHERF. These findings reveal that NHERF can directly bind to the PDGFR and potentiate PDGFR activity, thus elucidating both a novel mechanism by which PDGFR activity can be regulated and a new cellular role for the PDZ domain-containing adapter protein NHERF.